A comparative study on the mechanical and structural design of nacre in gastropod and bivalve molluscs. (February 2021) - Goswami, A.
Abstract: The lesson learnt from nature is presented through the examination of shells from four mollusc species (two gastropods and two bivalves). Individual aragonite tablets together with the organic network have been studied in terms of tablet dimensions, tablet stacking sequence, texture and the weight fraction of the organic present in these bio-composite shells. Mechanical properties viz. elastic modulus and hardness at the macro (bulk), micro (tablet) and nano (aragonite nanograins) levels have been determined using the experimental technique of nanoindentation together with the theoretical formulations offered by the Mori-Tanaka method and other such mechanical models for composites. XRD studies confirm the strong c-axis crystallographic orientation - aligned parallel to the direction of growth and crystallization of nacreous tablets, and fractography performed on the shell specimens suggests a difference in the stacking of individual aragonite layers for the gastropod and bivalve molluscan class, respectively. DSC and TG-DTA data helped in characterizing the organic material present in the shell specimens and in calculating the organic weight and volume fractions across species. Further to this, the DSC data revealed that the nature of the organic in the brick and mortar assembly of nacre, was similar in nature across the two molluscan classes reported in this study. EBSD studies performed on our system revealed a difference in crystallographic texture for the two different tablet stacking (columnar and sheet nacre). It has been shown experimentally that the shells of gastropods (columnar nacre) are orthotropic in nature, while the bivalve mollusc shells (sheet nacre) are anisotropic in nature.